Ekstraksi Zat Warna dari Kulit Kayu Galam (Melaleuca leucadendron Linn) dan Evaluasi dalam Pewarnaan Kain Satin (The Extraction of Natural Dyes from Galam (Melaleuca leucadendron Linn) Bark and The Evaluation on Satin Dye Application) - Rinne Nintasari; Djoko Purwanto (Jurnal Riset Industri Hasil Hutan, 2016)
Galam bark has not been widely used, it was only stacked and burned. Tree bark usually contains lignocellulose and natural dye. This study aimed to evaluate the application of galam bark for natural dyes on fabric. Galam bark was extracted using soxhlet and maceration methods, with time and solvent extraction variations. The obtained natural dye was used for dyeing using lime and alum for fixation. The results showed that the soxhlet extraction with water as the solvent for 5 hours produced dye with pH value 7 (neutral) and color sharpness 21 PtCo. The soxhlet extraction with water as the solvent for 7 hours produced dye with pH 5 (acid) and the highest color sharpness 68 PtCo. The most favorable color (value 3.3) was obtained from the soxhlet extraction technique with alum fixation. The highest color adsorption value (1.95%) was obtained from the lime fixation process. The natural dye extracted from Galam bark produced color sharpness, dyes and color absorption that had not met the expected result.Keywords: galam bark, extraction, dye, fabric dyeing